3D bioprinted organ‐on‐chips - Sajjad Rahmani Dabbagh; Misagh Rezapour Sarabi; Mehmet Tugrul Birtek; Nur Mustafaoglu; Yu Shrike Zhang; Savas Tasoglu (Aggregate, 2023)
Abstract Organ‐on‐a‐chip (OOC) platforms recapitulate human in vivo‐like conditions more realistically compared to many animal models and conventional two‐dimensional cell cultures. OOC setups benefit from continuous perfusion of cell cultures through microfluidic channels, which promotes cell viability and activities. Moreover, microfluidic chips allow the integration of biosensors for real‐time monitoring and analysis of cell interactions and responses to administered drugs. Three‐dimensional (3D) bioprinting enables the fabrication of multicell OOC platforms with sophisticated 3D structures that more closely mimic human tissues. 3D‐bioprinted OOC platforms are promising tools for understanding the functions of organs, disruptive influences of diseases on organ functionality, and screening the efficacy as well as toxicity of drugs on organs. Here, common 3D bioprinting techniques, advantages, and limitations of each method are reviewed. Additionally, recent advances, applications, and potentials of 3D‐bioprinted OOC platforms for emulating various human organs are presented. Last, current challenges and future perspectives of OOC platforms are discussed.